Damping Parameters Identification of Cabin Suspension System for Heavy Duty Truck Based on Curve Fitting - Leilei Zhao; Changcheng Zhou; Yuewei Yu (Shock and Vibration)
During the dynamic simulation of cabin system, the damping parameters values of cabin suspension are the key factors. In previous work, for obtaining all the parameters of the cabin system of trucks for long distance transport, a parameters identification model was built by minimizing the error of the root-mean-square acceleration between the tested and the measured. However, the identification precision is not high. In this paper, according to the real cabin system of a heavy duty truck for short distance transport, a 3-DOF model of cabin system was built. Based on curve fitting method, a new identification model for damping parameters was established. At last, the bench test was done and the comparisons were conducted among the tested values, the values identified by the method built in this work, and those obtained by the method built in previous work. The results show that the model built and the method proposed are feasible, and the identification precision is higher than the previous work.